OPTIMALISASI SUMBERDAYA HUTAN UNTUK KONSERVASI DAN KEMANDIRIAN DESA (Studi Inovasi Lokal dari Desa-Desa Indonesia Timur)OPTIMALISASI SUMBERDAYA HUTAN UNTUK KONSERVASI DAN KEMANDIRIAN DESA (Studi Inovasi Lokal dari Desa-Desa Indonesia Timur) - Kurniawan, Borni (Universitas Mahasaarswati Denpasar, 2012)
The welfare and prosperity are a great vision of Indonesian nation. One of strategies that have been taken by the government is to maximize the forest and land assets for the greatest prosperity of the people economically. But in one side, the unilaterally mastery that played by the country have many advantages for private groups and disadvantages for the village community. People want agrarian reform and redistribution assets as key policyto ensure the sustainability of village livelihoods. Unfortunately, the government was never realization of the policy completely. Currently, the innovation and emancipation local movement has been growing to develop the local resources as a response to the governments slowness to create national asset utilization policies that ensure the welfare of the village community. So, it is the time for the government to recognize the villages as the identity of the nations that whose ability to manage the natural resourcescan be accounted, even though the recognition is in theform of the delegation of local scale authority from the supra government of village to the village.The welfare and prosperity are a great vision of Indonesian nation. One of strategies that have been taken by the government is to maximize the forest and land assets for the greatest prosperity of the people economically. But in one side, the unilaterally mastery that played by the country have many advantages for private groups and disadvantages for the village community. People want agrarian reform and redistribution assets as key policyto ensure the sustainability of village livelihoods. Unfortunately, the government was never realization of the policy completely. Currently, the innovation and emancipation local movement has been growing to develop the local resources as a response to the governments slowness to create national asset utilization policies that ensure the welfare of the village community. So, it is the time for the government to recognize the villages as the identity of the nations that whose ability to manage the natural resourcescan be accounted, even though the recognition is in theform of the delegation of local scale authority from the supra government of village to the village.